"EVIDENCED BASED DIAGNOSTIC PROTOCOL AND MANAGEMENT FOR PAIN IN RIGHT ILIAC FOSSA" - Dr.Jitendra Kumar Saroj; Professor Dr. Abhay bhatnagar; Dr.Ganesh Chandra yadav (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND; Right iliac fossa pain is most common clinical presentation encountered in surgical opd. Usually during evaluation, diagnosis is uncertain in some cases and patient suffers a lot. Clinical symptoms usually not involved during evaluation of patient this also makes diagnosis more difficult. Therefore aim of the study was that how we will proceed in this caseMETHOD AND METHOD; this was prospective study and total 30 patients were analyzed. Study was done at tertiary centre. All patients suspected with pain in right iliac fossa included in this study. First evaluated clinically then biochemical and radiological investigated. Histological and acid fast bacilli culture was not included. Diagnostic laparoscopy was not included in this study RESULTS; out of 30 cases, acute appendicitis were in 15 cases (50%), followed by appendicular lump( 7 cases ,23%), irritable bowel disease (3 cases,10%),tubercular lesion (2 cases,6.7%),carcinoma of caecum (1 case,3.33%), appendicular abscess(1 case,3.33%) , both appendicitis with tubercular lesion were also present (1 case,3.33%). All cases of acute appendicitis, appendicular lump, carcinoma of caecum were managed surgically while appendicular abscess and ilieocaecal tuberculosis was managed conservatively.CONCLUSION; pain in right iliac fossa is very common presentation of many diseases therefore diagnostic evaluation of right iliac fossa pain is very difficult. It varied widely with age and sex especially in female is very cautious during clinical evaluation. Even CT scan is still unclear about the diagnosis and till date no definite diagnostic protocol has made. This study suggest a protocol for management of pain in right ilac fossa but before validate this protocol, a large data must be needed.